The Effect of Using Think Pair Share on Students Reading Ability - Arief Maulana (Language-Edu, 2019)
The purpose of learning English does not run on certain scope of school, but it reaches all grades. The significant aim is enabled the student to communicate in English. A communication skill can be developed and reached through some elements which should be studied, there are major of skill, namely; speaking, reading, writing, and listening which are presented in the 2004 English curriculum. It cannot be realized which English is a part of communication, and used in the world. English is a foreign language especially in Indonesia which attached middle of formal school. That is why English is not only learnt in some countries, but also categorized as foreign which learnt for communication. In English teaching process, TPS can be used as an alternative way that can be applied in teaching English, including reading. This research will be conducted to find out the effect of Think Pair Share on student’s reading comprehension achievement. The experimental research is done with an assumption that Think Pair Share never applied at the eleventh class SMA 17 Agustus 1945 Banyuwangi. Through it is necessary to do a research entitled “The Effect of Using Think Pair Share on students reading ability. Reading is a complex dynamic process that involves the bringing of meaning to and the getting of meaning from printed page (Rubin, 1993:4). Basically, reading is a process of getting ingormation from written words. Reading passages usually tells about the aim to grasp the author’s idea. By reading is not simply process of getting the meaning of the printed.             The hypothesis is statistically stated there is significant difference in the reading comprehension achievement between students taught using think pair share technique and the conventional technique. The result of the analysis which is computed by using SPSS version 20, it was found that the value of Significance for teaching strategy .04, it can be concluded that sig. value (.04< .05) or it means that Ho is rejected and Hi accepted. “there is difference in students reading comprehension achievement between students taught using TPS and Conventional technique.Key words: effect, Think Pair Share, reading ability.Anderson, N. 1999. Exploring Second Language Reading. Issues and Strategies. Andrea. 2009. Narratives onTeaching and Teacher Education. United states:Palgrave mecmillan.  Brown, H, D. 2000. Principles of Language Learning and Teaching.Fourth Edition. The United States of America: Pearson Education, Inc. Brown, H, D. 2004. Language Assessment: Principles and Classroom Practices. The United States of America: Pearson Education, Inc. Brown, H, D. 2007. Principles of Language Learning and Teaching.Fifth Edition. The United States of America: Pearson Education, Inc. Brown, James Dean & Rodgers, Theodore. S. 2002. Doing Second Language Research.New York: Oxford University Press. Brown.2015.Teaching by principle An Interactive Approach to language Pedagogy.USA: Pearson Education. Douglas, E. 2005.Reading Comprehension Strategies for English Language Learners.Retrieved in http:///www.learnnc.org/lp/pages/ell-readcomp078-2#1. Fraenkel, J. R., & Wallen, N. E. (2008). How to design and evaluate research Lyman, F. 1981. The Responsive Class Discussion. Maryland: Oxford UniversityLyman. 1981. Strategies for Reading Comprehension Think Pair Share. Center for learning and teaching excellent: Arizona State University. Maryland.  M. Afan & Marheni, N. Dantes. 2013. The Effect of Think Pair Share Technique on the English Reading Achievement of the Students Differing in  chievement Motivation at Grade Eight of SMPN 13 Mataram. Bali: Program Pascasarjana IKIP Ganesa. Meng Jing. 2010. Cooperative Learning Method in the Practice of English Reading and Speaking. Journal of Language Teaching and Research, Vol. 1, No. 5, pp. 701-703. Finland: Academy Publicher. Michael. 2015. The Effect of Think Pair Share on the English Reading Text. Jakarta: Program IKIP. Pallan, Julie. 2007. Survival manual. Step by Step Guide to Data Analysis Using Spss For Windows Third Edition. New York: McGrow-Hill Company.  Ricard. 2002.Methodology in language Teaching. USA: Cabbridge UniversityRobertson, K. 2006. Increase Students Interaction by Think-Pair-Share Slavin. 2001. Cooperative Learning and Reading. America: Library of Public Univesity. Snow, Catherine. 2002. Reading for Understanding. America: RAND Publication.Technique. Mexico City: Colorin Colorado.